Efektivitas Penggunaan Analgetik dan Antibiotik pada Pasien Pasca Operasi Fraktur Tertutup di Instalasi Rawat Inap Bedah RSUD Arifin Achmad Provinsi Riau: Effectiveness of Usage Analgetics and Antibiotics in post Surgical Patients with Closed Fractures in Surgical Department of Arifin Achmad Tertiary Hospital in Riau Province - Fridelly Mairani Apt; Fatma Sri Wahyuni; Hansen Nasif (LPPM Universitas Abdurrab, 2023)
The aim of this study was to examine sociodemographic features, visual analogue scale (VAS) scores before and after administration of analgesics, the effectiveness of the use of analgesics and antibiotics. This research uses descriptive analysis method with prospective cross sectional design. Data collection was carried out prospectively with direct observation of the pain felt by the patient using a VAS card at the 24th hour after surgery and after administration of analgesics. Observations were made on the patient's surgical wound on days 3-7 to 30 days postoperatively to observe the presence or absence of ILO. Of the 40 patients studied, the most age was 26 to 35 years (27.77%), the least were 45 to 55 years (11.11%) and 56 to 65 years (11.11%) ). Based on gender, 27 people (67.50%) were male and 13 people (32.50%) were female. Out of 40 patients, 39 patients (97.5%) did not have ILO and 1 patient (2.5%) had ILO. Before administration of analgesics all patients experienced pain. After administration of paracetamol infusion in 8 patients, ketorolac injection in 31 patients, and tramadol injection in 1 patient, the pain scale decreased. Data analysis using the Wilcoxon test showed the effectiveness of the use of analgesics on changes in the pain scale in patients (p <0.05) and descriptive analysis showed that there was effectiveness in the use of antibiotics in postoperative closed fracture patients.